KOMPETENSI PEDAGOGIK YESUS BERDASARKAN MATIUS 5-7 DAN IMPLEMENTASINYA DALAM PELAYANAN SEKOLAH MINGGU - Simon Runtung; Rini Bunga (SEKOLAH TINGGI TEOLOGI KIBAID, 2021)
Jesus Christ is the Great teacher of great influence. Every teacher who wants to be successful must learn from Jesus who has pedagogical competence based on Matthew 5-7. The purpose of this study was to find the reasons why Jesus 'pedagogical competence based on Matthew 5-7 had not had a maximum impact and to find the implementation of Jesus' pedagogical competence in Sunday school teaching at the KIBAID Church in Tombang Congregation. The research method used is qualitative with data collection techniques through observation and interviews. The informants involved were pastors, elders, Sunday school teachers, and parents. The results showed that the cause of Jesus' pedagogical competence based on Matthew 5-7 had not had a maximum impact on Sunday School teaching in the KIBAID Church of the Tombang Congregation due to lack of lesson planning preparation, lack of skill in choosing and using appropriate teaching strategies, lack of creativity in developing teaching methods. Therefore, it is necessary that Jesus' pedagogical competence based on Matthew 5-7 needs to be implemented with full love and attention to students, able to direct students, base teaching with prayer, and guide students to practice the truth.